OPTIMUM SALINITY LEVEL FOR THE CULTIVATION OF CILIATED PROTOZOA - MUKAI, YUKINORI; MOHD SHAHIDIN, SYAFIQAH HANANI; MOHMAAD NOOR, NORMAWATY (Malaysian Applied Biology, 2020)
In the present study, protozoa was cultured in different salinity water (10%, 20% and 30%) to determine the optimum salinity level required for the culturing. We examined the densities of protozoa and the ciliates Euplotes spp. in a general culture and Euplotes encysticus Yonezawa in a separate monoculture. Various species of protozoa were observed in the culture water, with a peak density of 30,000–40,000 cells ml–1 on day 4. The density of Euplotes spp. in the culture water increased with elapsed days, peaking on day 3. One-way analysis of variance showed a significant difference in the densities on day 3, and post-hoc Tukey–Kramer test results showed that the density at 10% was significantly higher than that at 30%. The E. encysticus monoculture peaked at 5000–6000 cells ml–1, but there was no significant difference between the salinity levels. Although our results are not definitive, the lower salinity level appeared most suitable for culturing protozoa. The ciliated protozoa Euplotes spp. in the current study were smaller than 100 µm, and they may be suitable size as live feed as starter diet for marine fish larvae with small mouth openings